A Theoretically Psychological Analysis of Semantic Representation of Bilinguals’ Mental Lexicon - Zhang, Qi (JOURNAL OF ADVANCES IN LINGUISTICS, 2022)
Due to the limitations of the existing research methods per se, studies probing into the semantic representation of bilinguals’ mental lexicon from the dimension of metrology yield no convincing results. This paper explores the semantic representation of bilinguals’ mental lexicon by analyzing the relationship between language and thoughts, the production of language from a theoretically psychological perspective. Such a conclusion can be drawn that 1) there is but one semantic system shared by natural languages and 2) the semantic information of mental lexicon is not attached to one specific vocabulary but stored separately in the cognitive system. The study of the semantic representation of bilinguals’ mental lexicon is conducive to the investigation into the universality and particularity of language itself and to the exploration of the nature of language, thought and human behavior.